Initial investigation of efficacy and safety of a new dipeptidyl peptidase-4 inhibitor, gosogliptin, for type 2 diabetes in Russia - Lyudmila Viktorovna Nedosugova; Nina Alexandrovna Petunina; Karina Oganesovna Galstyan (Сахарный диабет)
Current treatment strategies for type 2 diabetes mellitus (T2DM) are based on using safe and effective hypoglycaemic agents for preventing diabetic vascular complications and reducing the risks associated with weight gain and hypoglycaemia. These goals may be achieved using new agents with a fundamentally new mechanism of action: inhibitors of dipeptidyl peptidase-4 (DPP-4i). However, the wide distribution of this enzyme in the body is associated with extraglycaemic DPP-4i effects, both positive and negative. Thus, it is important to develop and implement new DPP-4i agents for clinical practice. Aim. To investigate the efficacy and safety of a novel DPP-4i, gosogliptin, for use as monotherapy and in combination with metformin vs. vildagliptin as monotherapy and in combination with metformin for patients with drug-naive type 2 diabetes in a multicentre, open, randomized clinical trial. Materials and methods. We enrolled 299 drug-naive type 2 diabetes patients; 149 patients were randomized to receive gosogliptin and 150 patients received tovildagliptin. These groups had similar baseline characteristics. After randomization, 12 weeks of monotherapy was administered to both groups. Further, it was decided to continue the monotherapy or in combination with metformin, depending on each patient. The results after the first 12 weeks are presented in this paper. Results. After 12 weeks of monotherapy, HbA1c levels decreased significantly from 8.61% to 7.41% (p